Transcriptome Analysis of Two Different Developmental Stages of Paeonia lactiflora Seeds. (7th August 2017) - Ma, Yonglei; Cui, Jinqiu; Lu, Xiujun; Zhang, Lijie; Chen, Zhijing; Fei, Riwen; Sun, Xiaomei
Abstract : Paeonia lactiflora is a herbaceous flower in the family Paeoniaceae with both hypocotyl and epicotyl dormant seeds. We used high-throughput transcriptome sequencing on two different developmental stages of P. lactiflora seeds to identify seed dormancy and germination-related genes. We performed de novo assembly and annotated a total of 123, 577 unigenes, which encoded 24, 688 putative proteins with 47 GO categories. A total of 10, 714 unigenes were annotated in the KEGG database, and 258 pathways were involved in the annotations. A total of 1795 genes were differentially expressed in the functional enrichment analysis. The key genes for seed germination and dormancy, such as GAI1 and ARF, were confirmed by quantitative reverse transcription-polymerase chain reaction analysis. This is the first report of sequencing the P. lactiflora seed transcriptome. Our results provide fundamental frame work and technical support for further selective breeding and cultivation of Paeonia . Our transcriptomic data also serves as the basis for future genetics and genomics research on Paeonia and its closely related species.